Design of Control Strategy and Effect Evaluation for Primary Frequency Regulation of Wind Storage System - Li, Cuiping; Zhang, Zheshen; Li, Junhui; Ma, Yunbao; Zou, Jiajun (Frontiers in Energy Research, 2021)
Because of wind sources’ volatility and intermittent news, wind power has made a more and more heavy burden on the power system. This paper analyzes in detail the traditional control method, parallel control strategy and serial control strategy of the wind storage system, and combines the advantages of the two to propose an optimal control strategy. A comprehensive performance evaluation method for the primary frequency regulation of the ESS participating in the power grid is proposed based on the power system operation requirements. In the example, the frequency modulation performance of the optimal control strategy is verified by the evaluation method described in this paper in the Chinese frequency adjustment market.